College students’ perceptions about academic institutions’ support for diversity and inclusion in Pakistan - Maham Muzamil; Maria Shiraz; Farzana Iqbal; Gulzar H. Shah; Masha Asad Khan (Cogent Education, 2024)
Educational institutions that prioritize diversity and inclusion initiatives can enhance students’ sense of involvement and belonging, irrespective of demographic differences. This study aims to explore how college students in Pakistan perceive their academic institutions’ support for diversity and inclusion. Convenience sampling was used to select 1004 students from among 595 colleges in Lahore City through primary data collection and a cross-sectional survey. We used ANOVA to evaluate how students perceived institutional support for diversity and inclusion in five different diversity categories. We conducted pairwise comparisons to identify significant differences in mean scores related to the characteristics of each independent variable in students’ perceptions of institutional support for diversity. We found statistically significant associations (p < 0.05) between diversity and inclusion and institutional support of cultural diversity, specifically concerning socioeconomic status, political ideologies, ethnic background, caste and religion at the college level. Significant differences were observed in students’ perceptions of institutional support for diversity and inclusion across groups with equal levels of support, including differences based on institution type, mother tongue, monthly household income and age. Irrespective of ethnic differences, educational institutions that prioritize diversity and inclusion can enhance students’ sense of engagement and belonging.